European Climate Change Perceptions: Public support for mitigation and adaptation policies. (30th December 2015) - Hagen, Bjoern; Middel, Ariane; Pijawka, David
Abstract: This paper presents results from a large multi‐country study focusing on public perceptions of climate change and relevant mitigation and adaptation policies in Spain, Netherlands, UK and Germany. The purpose of this paper is two‐fold: first, to understand the nature of public perceptions of global climate change in different countries; and secondly, to gauge the public's support of climate change measures in terms of mitigation and adaptation policies. Our analysis shows high levels of public indecisiveness regarding the danger climate change poses, which source of climate change information to trust and whether to support any mitigation or adaptation strategies. The high levels of uncertainty present an opportunity to increase policy support and foster behavioural changes in the future through well‐designed communication programmes. Therefore, this study has identified several aspects that need to be considered in future communication programmes. Copyright © 2015 John Wiley & Sons, Ltd and ERP Environment